PENINGKATAN KETERAMPILAN MENYUSUN TEKS CERITA SEJARAH MENGGUNAKAN STRATEGI GENIUS LEARNING MATA PELAJARAN BAHASA INDONESIA PADA KELAS XII MIPA 1 DI SMAN 8 CIREBON : PENILAIAN TINDAKAN KELAS - Dewi Sundayani (Jurnal Tuturan, 2019)
The purpose of this research is to improve the skills of composing historical narrative texts of XII MIPA 1 students of SMAN 8 Cirebon school by applying genius learning strategy. Through genius learning model, the improvement can be seen through the process or product.The research subject is 25 students of XII MIPA 1 of SMAN 8 Cirebon. The model which used is Classroom Action Research. Action and implementation procedure at research site divided into two cycles. Three meeting took place in each cycle. This research focused on problems related to the skills improvement in composing historical narrative text by applying genius learning strategy. Qualitative description and qualitative are the techniques which used in analysing the data.The successful criteria achieved by students in this research are seen from the better changes and the improvement in studying activity also the result in practice composing historical narrative text.The research findings show as follows. First, the application of genius learning strategy can improve the quality of learning process in composing historical narrative texts. There is an improvement in some aspects, such learning situation, students focus, and activeness which makes better improvement and makes learning how to compose historical narrative text more interesting and fun. Second, learning how to compose historical narrative texts by applying genius learning strategy can improve the result of composing historical narrative texts ability.It is seen from the average score of composing historical narrative text ability of cycle one an action is 64.53, while after given an action in cycle two the average become 85.00. It shows that there have been increased 20.47 points. At the end of cycle two, every aspects and criteria for composing historical narrative text shows significant improvement. Based on the result above, it is known that the application of genius learning strategy is successful and can improve the ability of composing historical narrative text of XII MIPA 1 students of SMAN 8 Cirebon.